Emprego de miniparafusos na sutura palatina mediana como ancoragem ortodôntica: relato de caso - Morais, Hécio Henrique Araújo de (2006)
The midpalatal area with thin, keratinized soft tissue and sufficient cortical bone is an optima site for miniscrew implantation. Even though the midpalatal area has its own anatomical limitations, these can be overcome by the bonding of extension arms to the miniscrews. Such a technique can also be effectively used for intrusion of upper molars with reduced treatment time and enhanced comfort